(untitled) (Universal International Scientific Journal, 2026)
This article analyzes the development of critical thinking in students based on the PIRLS tasks, its essence, scientific and theoretical description, functions and social principles, methods used in the development of critical thinking, the main directions of developing critical thinking in the educational process and its descriptions in the relevant literature. It presents the scientific views of pedagogical psychologists, ethicists, and political scientists on modern diagnostic methods and educational mechanisms that should be used to diagnose critical thinking in children studying in primary grades, which is the main stage of the continuous education system.